Differential elements in Silesian toponyms with the Berg / góra component - Lech-Kirstein, Danuta (Papers in Linguistics, 2025)
The article concerns Silesian geographical names featuring the component Berg / góra (‘mountain’) and the differential elements. The analysed onomastic material comes from Słownik etymologiczny nazw geograficznych Śląska [Etymological Dictionary of Geographical Names of Silesia] and includes names of originally German and Polish origin, as well as new Polish names altered by the Commission for Determining Place Names after World War II. The study aims to compare the methods of compound name creation in Polish and German. Using the methodology of linguistic image of the world, the research demonstrates how these names reflect interpretations and classifications of reality, hierarchies of values, and an anthropocentric perspective on the world. Polish and German names interwoven in Silesia, although distinct from the perspective of word-formation, share similar differential elements that describe the size and shape of an object, its location, topographical characteristics, the presence of fauna and flora, or the relationship between the object and humans. They may also serve as reflections of material or spiritual culture. Silesia emerges as a region of rich symbolism and diverse linguistic and cultural heritage. Findings of the study indicate that the linguistic images of the world represented by the discussed toponyms in both languages are similar to each other and coherent.